P3.75 Viral suppression in late presenting hiv-infected pregnant women. (8th July 2017) - Xavier-Souza, E; Nóbrega, I; Timbó, MS; Barone, C; Fernandes, S; Netto, E; Travassos, AG
Abstract : Introduction: The maternal HIV viral load (VL) is a major predictor of mother to child transmission (MTCT). Therefore, it is necessary a rapid decrease of VL among late-presenting (LP) (after 28 weeks) pregnant women living with HIV (PWLH) aiming viral suppression (VS). We aimed to identify the population of LP-PWLH and compare the VS to the group who had earlier access (EA) to prenatal care. Methods: A retrospective cohort carried out at the major HIV reference centre in Bahia, Brazil. Medical records of PWLH attended at prenatal care were reviewed from January 2011 to December 2013. HIV VL and TCD4+ count data were obtained from the national database. Statistical analyses were performed with SPSS 20.0. Results: A total of 235 PWLH enrolled in the study, of which 29.4% were LP. Among the latter, the mean age was 28.3 (±6.9) years, similar to the EA group. Thirty four percent of the LP had <8 schooling years (p=0.16), 40.7% were single (p=0.64), 24.6% reported alcohol use (p=0.15), 1.6% drug use (p=0.44) and only 16.7% regular condom use (p=0.92). The majority of LP (62.9%) had partners with unknown serological status, 25.7% had seroconcordant and 11.4% had serodiscordant partners (p<0.01). LP predominantly had HIV diagnosis during pregnancy (60.9%; p<0.01) and were ARV naïve (78.3%; p<0.01), while only 14.5% were on ART at conception (p<0.01). As for the initial ART regimen during pregnancy, 89.9% of LP were using a protease inhibitor based regimen and 11.6% had had regimen changes during pregnancy (p=0.36). LP had a higher initial VL (log10 3.4; p<0.01) and those with recent diagnosis also had higher VL (log10 3.8; p=0.02). LP were more likely to not have a second VL during pregnancy or early peripartum (33.3%; p<0.01). VS was less achieved (34.8% vs 71.8%; p<0.01; OR 4.7, CI95% 2.36–9.66) by the LP group. Conclusion: LP showed an increased risk of MTCT, with recent HIV diagnosis, higher VL at prenatal onset and a lower rate of VS. Thus, the use of integrase inhibitors would be a better choice for this population, since it promotes a quickly decrease of VL.